Increased but not pristine soil organic carbon stocks in restored ecosystems - Irene Ascenzi; Jelle P. Hilbers; Marieke M. van Katwijk; Mark A. J. Huijbregts; Steef V. Hanssen (Nature Communications)
Abstract Ecosystem restoration can contribute to climate change mitigation, as recovering ecosystems sequester atmospheric CO2 in biomass and soils. It is, however, unclear how much soil organic carbon (SOC) stocks recover across different restored ecosystems. Here, we show SOC recovery in different contexts globally by consolidating 41 meta-analyses into a second-order meta-analysis. We find that restoration projects have, since their inception, led to significant SOC increases compared to the degraded state in 12 out of 16 ecosystem-previous land-use combinations, with mean SOC increases thus far that range from 25% (grasslands; 10–39%, 95% CI) to 79% (shrublands; 38–120% CI). Yet, we observe a SOC deficit in restored ecosystems compared to pristine sites, ranging from 14% (forests; 12–16% CI) to 50% (wetlands; 14–87% CI). While restoration does increase carbon sequestration in SOC, it should not be viewed as a way to fully offset carbon losses in natural ecosystems, whose conservation has priority.